2019
DOI: 10.1007/s00227-019-3560-y
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking intraspecific variation in offspring responses to multiple environmental drivers

Abstract: Understanding organismal responses to environmental drivers is relevant to predict species capacities to respond to climate change. However, the scarce information available on intraspecific variation in the responses oversimplifies our view of the actual species capacities. We studied intraspecific variation in survival and larval development of a marine coastal invertebrate (shore crab Carcinus maenas) in response to two key environmental drivers (temperature and salinity) characterising coastal habitats. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 67 publications
4
34
0
Order By: Relevance
“…The most likely underpinning mechanism is an increase in osmoregulatory capacity at higher temperatures: thus, TMLS may be a consequence of this physiological plasticity. The TMLS is found in other coastal species and it is relevant in the light of climate change in that (moderate) warming may favour expansion towards coastal areas characterized by moderately low salinities [36]. However, the same study also found that responses vary among larvae from different females [36], which may be driven by variability in the maternal environment, for instance by the temperature and salinity experienced by females and embryos.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The most likely underpinning mechanism is an increase in osmoregulatory capacity at higher temperatures: thus, TMLS may be a consequence of this physiological plasticity. The TMLS is found in other coastal species and it is relevant in the light of climate change in that (moderate) warming may favour expansion towards coastal areas characterized by moderately low salinities [36]. However, the same study also found that responses vary among larvae from different females [36], which may be driven by variability in the maternal environment, for instance by the temperature and salinity experienced by females and embryos.…”
Section: Introductionmentioning
confidence: 83%
“…The TMLS is found in other coastal species and it is relevant in the light of climate change in that (moderate) warming may favour expansion towards coastal areas characterized by moderately low salinities [36]. However, the same study also found that responses vary among larvae from different females [36], which may be driven by variability in the maternal environment, for instance by the temperature and salinity experienced by females and embryos. Theoretically, salinity and temperature may alter embryonic developmental processes and hence modify larval performance in many possible ways.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Relevant examples to climate change are, for instance, synergistic effects of increased temperature combined with food limitation or elevated CO 2 (i.e., the combined effect of both stressors is larger than the sum of each separate effect: Giebelhausen & Lampert, 2001;Przeslawski et al, 2015;Schiffer et al, 2014;. By contrast, increased temperature and reduced salinity can operate antagonistically: That is, warming appears to mitigate the negative effects of low salinity (or other drivers) on the performance and fitness in some coastal marine organisms (Lange & Marshall, 2017;Spitzner et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we use our results and information from the literature to propose a testable hypothetical model linking osmoregulation, interactive effects of temperature and salinity on organismal performance, and future changes in species distributions across coastal-estuarine gradients in response to warming. We first focus on the antagonistic effect called thermal mitigation of low salinity stress (TMLS: Spitzner et al, 2019) which is common in coastal-estuarine organisms (Anger, 1991;González-Ortegón & Giménez, 2014;Janas & Spicer, 2008;Kinne, 1971). TMLS is defined as the mitigation of the negative effects of exposure to low salinity on performance or fitness (e.g., survival) by increased temperatures.…”
Section: Introductionmentioning
confidence: 99%